Treatment-seeking behaviour among infertile tribal women of Palghar district in India - Jadhav, Arvind Santu; Govil, Dipti (Frontiers in Reproductive Health, 2023)
Background The tribal culture views health care practices differently from the mainstream. Infertile tribal women practice treatment-seeking behaviour that reflects the community's cultural access to and availability of treatment as well as customs to meet their health care needs. In the environment of rising awareness of infertility and numerous treatment options, this study aims to highlight the infertility treatment-seeking behaviour of tribal communities. Data and methods The study employed a mix methods approach to collect data from 153 tribal couples suffering with infertility (interview schedule) and the community (in-depth interviews—14 and focus group discussions—12). The data was analyzed using Stata 13.0, and NVivo 10. Results of the quantitative data were triangulated with qualitative data for writing. Results Many treatment options were available for infertility in the community. Generally, traditional healers (98.7%) were preferred over modern healthcare practitioners (35%). Community members usually guided infertile couples for choosing providers. Treatment practices were very different among primary infertile women than sub-fertile. Women frequently discontinued treatment and switched between providers because of unaffordability, poor connectivity, distance, travel time, time constraints, and non-supportive circumstances. The couples were advised to consume herbs, and eat or avoid certain food items, were given massage, burns on the abdomen (dagani), removed black blood (phasani) and other various rituals to appease spirits, get rid of ghosts while offering animal sacrifice, and conducting shidwa ritual. The mean expenditure on treatment was INR 18,374. If treatment did not yield any result, couple resorted to add another wife, divorce, accept childlessness and foster a child. Conclusion Local authorities should strive to work towards the socio-economic development of the tribal communities and provide good healthcare services at their doorstep. The infertility problem needs to be understood in the context of poverty, tribal beliefs, and unequal access to healthcare resources.